The Effect of Using English Song as Teaching Media to Improve Vocabulary Mastery on The Eleventh Grade Students of SMK Negeri 11 Samarinda - Purnamasari Purnamasari (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
The purpose of this study was to determine whether there was a significant difference in vocabulary mastery between students in the eleventh grade at SMK Negeri 11 Samarinda who used English songs and those who used conventional methods. Cluster random sampling was employed in this study, which is a strategy for determining sample size based on a group's cluster and homogeneous samples. Sixty pupils in the eleventh grade were engaged in this investigation. The research subjects were chosen at random and divided into two groups: experimental and control. Descriptive and inferential statistical approaches were used to obtain the data. Prior to conducting the hypothesis test, the normality and homogeneity tests were undertaken, and the hypothesis was tested using a t-test. The study's findings indicate that there is a significant difference between using English songs and traditional methods taught by the teacher for eleventh-grade students, with a significance value of 0,000 less than 0,05 and a t-value greater than the t-table, or 7,421 greater than 2,002, indicating that the use of English songs as a teaching medium is sufficiently effective to increase learning results.